Reconstruction of The Pot Fishing Gear Escape Gap Against The Catch - Tuhumury, Julian; G Hehanussa, Kedswin; Haruna, Haruna (Agrikan Jurnal Agribisnis Perikanan, 2022)
Fishermen use the pots based on their construction that operated from then until now.The catch is most small fish target and unfish target. The objective of this study was to analysiz the effectiveness of ascape gap of pots. The study was conducted from September to November 2021 in the waters of Ambon Island. Data collected in the form of type, number (tail), total length (cm), and body circumference of fish (cm) from the catch at each hauling. The results showed that the total number of catches as many as 20 trips is 154 fish that escaped amounted to 114 fish. The size of 2 cm fish that escaped amounted to 17 tails, the size of 2.5 cm amounted to 44 tails and the size of 3 cm amounted to 53 tails while the fish that did not escape amounted to 40 tails. The chance of catching fish that escaped at a gap of 2 cm is 11%, at a gap of 2.5 cm is 29%, at a gap of 3 cm is 34% while those who do not escape are 26%. The chances of fish escaping are determined by body depth, body girth and The Shape of the escape gap.